PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - I Ketut Suparya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The objectives of this study are to describe the difference of students’ achievement andcritical thinking in science subject by using Think Talk Write Strategy which is followed byconventional learning; to describe students’ outcome in learning science by using both strategiestype talk write strategy and conventional one; to describe students’ critical thinking by usingboth strategies, type talk write and conventional learning. This study is an quasi-experimentresearch which uses randomized post-test only control group design at 4 grade students in SDGugus IV Abiansemal District. By using a random pair of equal groups, the 4 grade students’ inSD N 4 Abiansemal, which consist of 31 students, is selected as experiment group and for thecontrol group is the 4 grade students’ in SD N 3 Abiansemal, which consist of 33 students.Analysis of research using one-way Manova shows: 1) learning outcomes and critical thinkingskills students who follow the TTW type cooperative learning model are significantly higherthan students who follow conventional learning models proven from the F value for Wilks lambdahas a significance smaller than 0,05, 2) Student learning outcomes in science learning thatfollow the TTW type of cooperative learning model is higher than conventional learning this isevidenced by the statistical value F = 8,918 with a significance level smaller than 0,05. 3)Students’ critical thinking ability in science learning that follows the TTW type of cooperativelearning model is higher than conventional learning, this is evidenced by the statistical value F= 14,732 with a significance level less than 0,05.Keywords: Cooperative Learning, Think-Talk-Write Strategy, Conventional Learning,Achievement, and Critical Thinking Skills